2017
DOI: 10.4236/ym.2017.12008
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies of Stem Cell Transplantation for Liver Cirrhosis

Abstract: Liver transplantation is widely regarded as the most effective therapy for end-stage liver diseases. However, stem cell-based therapy is being developed as a promising strategy which offers a number of benefits as it is minimally invasive and associated with low immunogenicity and low cost. This paper will review the major clinical issues surrounding the use of stem cell therapy for managing cirrhosis, such as discussing the selection of appropriate subtypes of bone marrow stem cells and the need for pre-diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Because EPCs share some characteristics of hematopoietic stem cells (HSCs), the indications for their treatment can be referred to HSCs [4]. However, some studies suggested that EPCs not only activate hepatic stellate cells to participate in the formation of fibrosis [5], but also contribute to sinusoidal endothelial vascular proliferation and promote liver fibrosis, thus aggravating portal hypertension [6].…”
Section: Mini Reviewmentioning
confidence: 99%
“…Because EPCs share some characteristics of hematopoietic stem cells (HSCs), the indications for their treatment can be referred to HSCs [4]. However, some studies suggested that EPCs not only activate hepatic stellate cells to participate in the formation of fibrosis [5], but also contribute to sinusoidal endothelial vascular proliferation and promote liver fibrosis, thus aggravating portal hypertension [6].…”
Section: Mini Reviewmentioning
confidence: 99%